1970
DOI: 10.1099/00221287-60-3-335
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Germination of Bacterial Spores by Hydrostatic Pressure

Abstract: S U M M A R YHydrostatic pressure initiated germination of bacterial spores in nutrientfree media. Those spores which were most dormant towards chemical germinants at I atmosphere pressure were also the most resistant to germination by pressure treatment. Germination by high pressure treatment was characterized by temperature and pH optima, like germination at atmospheric pressure. Germination initiated by pressure was inhibited by metabolic poisons and was potentiated by low concentrations of various nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1
2

Year Published

1971
1971
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(103 citation statements)
references
References 9 publications
4
96
1
2
Order By: Relevance
“…This alleviation of the specific requirements for germination was also apparent with regard to the requirement for inorganic ions. Alleviation of specific requirements for amino acids has been observed with Bacillus cereus in the presence of inosine or at high atmospheric pressures (Gould & Sale, 1970) and with B. megaterium after heating (Levinson & Hyatt, I 962). However, as germination of Bacillus spores can usually be initiated by any one of several amino acids, the germinative properties of mixtures of amino acids have been little studied, although in the presence of L-alanine there was no stimulation of the germination rate of B. subtilis var.…”
Section: Discussionmentioning
confidence: 99%
“…This alleviation of the specific requirements for germination was also apparent with regard to the requirement for inorganic ions. Alleviation of specific requirements for amino acids has been observed with Bacillus cereus in the presence of inosine or at high atmospheric pressures (Gould & Sale, 1970) and with B. megaterium after heating (Levinson & Hyatt, I 962). However, as germination of Bacillus spores can usually be initiated by any one of several amino acids, the germinative properties of mixtures of amino acids have been little studied, although in the presence of L-alanine there was no stimulation of the germination rate of B. subtilis var.…”
Section: Discussionmentioning
confidence: 99%
“…48) Pressures of 100-300 MPa activate the nutrient receptors whereas higher pressures of 500-800 MPa release the Ca 2þ -DPA depot. 46,49,50) The results of these studies give new insight into the mechanism of spore germination as well as contributions to food processing technology by high-pressure treatment. Table 2 lists the occurrence of yeast physiology and survival under high hydrostatic pressure.…”
Section: Recent Advanced Studies Of the Effects Of High Pressurementioning
confidence: 99%
“…45) Spores of Bacillus species are germinated by a variety of stimuli including nutrients, some chemicals and mechanical treatments such as abrasion and high pressure. [46][47][48] Nutrients trigger the receptors GerA, GerB and GerK in the inner membrane of the spore, followed by release of the Ca 2þ -dipicolinic acid (DPA) depot and activation of enzymes CwlJ and SleB. 48) Pressures of 100-300 MPa activate the nutrient receptors whereas higher pressures of 500-800 MPa release the Ca 2þ -DPA depot.…”
Section: Recent Advanced Studies Of the Effects Of High Pressurementioning
confidence: 99%
“…As for the synergism of ribosides with amino acids as germinants for Bacillus spores, Gould and Sale [6], from their study on the germinant action of hydrostatic pressure, have suggested that both riboside and pressure may function to increase the spore permeability to exogenous or endgenous a-amino acids. In this connection, Kaback and Milner [8] recently …”
mentioning
confidence: 99%